2023
DOI: 10.1073/pnas.2214080120
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting hate: The effect of deplatforming hate organizations on their online audience

Abstract: How does removing the leadership of online hate organizations from online platforms change behavior in their target audience? We study the effects of six network disruptions of designated and banned hate-based organizations on Facebook, in which known members of the organizations were removed from the platform, by examining the online engagements of the audience of the organization. Using a differences-in-differences approach, we show that on average the network disruptions reduced the consumption and producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Weighting the influence and discursive presence 30 , 178 , 179 of climate disinformation with the partial effectiveness of psychological inoculations, our findings join the recent discussion suggesting that behavioural science interventions do not seem to be efficacious enough to tackle systemic problems such as climate disinformation by themselves 59 , 60 , 180 – 182 . Systemic interventions, such as content moderation, virality circuit breakers 180 , deplatforming 178 , 183 or changing online engagement metrics towards the accuracy of information 184 , may be better at curbing climate disinformation. However, systemic actions are enforceable only by the same platforms that might be incentivized to let climate disinformation spread 184 – 190 .…”
Section: Discussionmentioning
confidence: 99%
“…Weighting the influence and discursive presence 30 , 178 , 179 of climate disinformation with the partial effectiveness of psychological inoculations, our findings join the recent discussion suggesting that behavioural science interventions do not seem to be efficacious enough to tackle systemic problems such as climate disinformation by themselves 59 , 60 , 180 – 182 . Systemic interventions, such as content moderation, virality circuit breakers 180 , deplatforming 178 , 183 or changing online engagement metrics towards the accuracy of information 184 , may be better at curbing climate disinformation. However, systemic actions are enforceable only by the same platforms that might be incentivized to let climate disinformation spread 184 – 190 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that compared to 2015, it is much more difficult for extremists and terrorists to operate on the biggest online platforms even if the different platforms do not have a 100% success rate in takedowns. According to various research products from multiple researchers in the field, deplatforming and takedowns related to individuals, influencers, organizations, and content from the jihadi movement and the extreme far-right when tested shows that after concerted and sustained efforts, there are diminishing returns for those trying to radicalize individuals online to their cause (Mirrlees, 2021;Thomas & Wahedi, 2023). 3 However, in the case of the jihadi movement, Conway, Khawaja, Lakhani, Reffin, Robertson, and Weir argue that there is a difference in the level of deplatforming when comparing the Islamic State to other jihadi organizations (Conway et al, 2019).…”
Section: Literaturementioning
confidence: 99%
“…Some have suggested that combining these soft remedies with "hard" remedies (15)-removing content and objectionable accounts (16)(17)(18)-could largely curtail misinformation spread (19). However, evidence for the short-term efficacy of hard remedies is mixed (20)(21)(22)(23)(24), and the long-term efficacy of these strategies has not been systematically examined. Hard remedies have also spurred accusations of censorship and threats of legal action (25, 26).…”
Section: Introductionmentioning
confidence: 99%